2014
DOI: 10.1093/gerona/glu106
|View full text |Cite
|
Sign up to set email alerts
|

Sildenafil Decreases BACE1 and Cathepsin B Levels and Reduces APP Amyloidogenic Processing in the SAMP8 Mouse

Abstract: The senescence-accelerated mouse-prone 8 (SAMP8), used as a model of aging, displays many established pathological features of Alzheimer's disease. Cognitive impairments and increased levels of hyperphosphorylated tau are found in the hippocampus of SAMP8 mice along with an increased β-secretase activity and amyloid-β (Aβ) depositions that increase in number and extent with age. Based on a previous study from our laboratory showing an amelioration of cognitive impairments and tau pathology by sildenafil, in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 83 publications
3
29
1
Order By: Relevance
“…Pifarré et al [142] also showed that the presence of astrocytes forming scar-like structures around infiltrates was enhanced by sildenafil, suggesting a possible mechanism for the restriction of the leukocyte dissemination in healthy parenchyma. However, this result does not corroborate other studies showing that PDE5-Is decrease GFAP expression and astrocyte activation [89,114,127,140].…”
Section: Multiple Sclerosiscontrasting
confidence: 99%
See 4 more Smart Citations
“…Pifarré et al [142] also showed that the presence of astrocytes forming scar-like structures around infiltrates was enhanced by sildenafil, suggesting a possible mechanism for the restriction of the leukocyte dissemination in healthy parenchyma. However, this result does not corroborate other studies showing that PDE5-Is decrease GFAP expression and astrocyte activation [89,114,127,140].…”
Section: Multiple Sclerosiscontrasting
confidence: 99%
“…due to differences between dose, duration of treatment, and animal models. In addition, both Akt/GSK3β and p25/CDK5 signaling are also involved in the regulation of Aβ [114], and it is possible that if the treatment was longer, this effect would be detected.…”
Section: Pde5-is' Beneficial Effects In Ad Through Creb/bdnf/arc Pathmentioning
confidence: 99%
See 3 more Smart Citations